Por uma ciência da linguagem no/do Brasil: percursos e irrupções teóricas - Ruiz, Marco Antonio Almeida (Universidade Federal de São Carlos, 2019)
For a long time, linguistics in Brazil developed, basically, from reflections undertaken from european and north american theoretical models, whose objective was to choose (or import) a certain vision about the language and apply it over data in brazilian portuguese. Currently, our linguistics – Brazil’s linguistics – perhaps more mature and established, count on its own models that take language as object of its reflection. So, it’s not about to highlight one theory or another, raising its positive or negative aspects, but to recognize that brazilian researchers drank from foreigner wells, adapting and utilizing whatever good they found in the best way possible. In a scientific paper, whose title is Uma teoria brasileira do idioma, published in the magazine Língua Portuguesa, on April 2012, Módolo and Braga wrote about some linguistic theories developed by brazilians knowledged in our last years’ territory. The authors highlight, e.g., the Gramática construtural da língua portuguesa from Back and Mattos (1972); the Sociolinguística paramétrica from Tarallo and Kato (1989); and the Abordagem multissistêmica from Ataliba Teixeira de Castilho (2010). Related to discourses’ field of study, we see constant reformulations and theoretical propositions that can be thought of in the brazilian way, such as the Semiótica da canção (Semiotics of the song), proposed by Luiz Tatit (2007); the Teoria do silêncio (Silence theory), from Eni Orlandi (2007); the Semântica do Acontecimento (Event Semantic), proposed by Eduardo Guimarães (2005); and the Teoria dos estereótipos básicos e opostos (Basic and Opposing stereotypes theory) from Sírio Possenti (2010). As an effect, such theories build their own theoretical objects differently, although taking discourse as object of observation. To this Ph.D. research, we understand discourse studies as a group of disciplines that has language, overlapped in its different orders (linguistics, enunciatives, historical) and expressed in distinct materialities (verbal, visual, verbal-visual), as an object of study. This way, based on theoretical assumptions from french discourse analysis, mainly on the thoughts about the notion of discourse event and narrative event, from Jacques Guilhaumou (2009), we have as objective to investigate the writing of discourse analysis’ history in our country, considering its different aspects and the different discourse flows that developed in our scenario after its reception and institutionalization in 1980, constituting it through a heterogeneous research network capable of composing a singular field, the discourse Studies. Thus, our corpus is composed of three brazilian discourse theory work, which are: Humor, língua e discurso (2010) from Sírio Possenti; Ironia em perspectiva polifônica (2008) from Beth Brait; and As formas do silêncio: no movimento dos sentidos (2007) from Eni Orlandi. Such narratives, beyond (re)visiting foreigner theories, aim towards providing new research methodologies from new angles’ perspectives, promoting reflections about the way of doing science itself – metadiscoursive event – and a particular way for brazilian discourse analysis.

Pendant longtemps, la linguistique au Brésil s’est essentiellement développée à partir de réflexions menées dans le cadre des modèles théoriques européens et nord-américains, dont le but était d'élire (ou d'importer) une certaine idée de la langue et de l'appliquer à des données en portugais. Actuellement, notre linguistique – la linguistique du Brésil –, peut-être plus mûre et établie, possède ses modèles propres qui prennent le langage comme objet de réflexion. Il ne s’agit donc pas pour nous de mettre l'accent sur l'une ou l'autre théorie, soulignant leurs points positifs ou négatifs, mais de reconnaître que les chercheurs brésiliens se sont abreuvés aux sources étrangères et les ont adaptées en profitant du meilleur de ce qui était bon. Dans un intéressant article de divulgation scientifique intitulé Uma teoria brasileira do idioma, publié dans la Revue Língua Portuguesa en avril 2012, Módolo et Braga parlent de certaines théories linguistiques développées par les chercheurs brésiliens ces dernières années, mettant notamment l'accent sur la Grammaire constructurale de la langue portugaise de Back et Mattos (1972), la Sociolinguistique paramétrique élaborée par Tarallo et Kato (1989) ou encore L’Approche multisystémique d’Ataliba Teixeira de Castilho (2010). Dans le domaine des études du discours, par exemple, nous observons des reformulations constantes et des propositions théoriques qui peuvent être considérées comme des approches « à la brésilienne », parmi lesquelles la Sémiologie de la chanson proposée par Luiz Tatit (2007), la Sémantique de l'événement d'Eduardo Guimarães (2005) ou la Théorie des stéréotypes de base et opposés (2010) de Sírio Possenti. Ces théories, bien qu'elles prennent chacune le discours comme objet d'observation, construisent leur objet théorique de façon tout à fait différente. Pour notre recherche de doctorat, nous entendons par études discursives un ensemble de disciplines qui prennent le langage, imbriqué dans ses différents ordres (linguistiques, énonciatifs, historiques) et manifesté dans différentes matérialités (verbales, visuelles, verbo-visuelles), pour objet d’étude. Dans ce sens, à partir des présuppositions théoriques de l'analyse du discours d’orientation française et, notamment, à partir des considérations sur la notion d’événement discursif et de récit de l'événement, proposées par Jacques Guilhaumou (2009), nous avons pour objectif d'investiguer l'écriture de l'histoire de l'analyse du discours dans notre pays, en prenant en considération les différents courants et les différentes théories qui se sont développés dans notre scénario après sa réception et son institutionnalisation en 1980, la constituant au moyen d’un réseau de recherche hétérogène capable de composer un champ singulier, celui des Études du discours. Ainsi, notre corpus est constitué de trois ouvrages de théories brésiliennes du discours, à savoir : Humor, língua e discurso (2010) de Sírio Possenti; Ironia em perspectiva polifônica (2008) de Beth Brait; et enfin, As formas do silêncio : no movimento dos sentidos (2007) d’Eni Orlandi. Ces récits, en plus de (re)visiter des théories étrangères, visent à proposer de nouvelles méthodologies de recherche sous de nouveaux angles, promouvant ainsi des réflexions sur la pratique scientifique elle-même – un événement métadiscursif – et une manière particulière de l’analyse de discours brésilienne.
Pour une science du langage au/du Brésil: parcours et irruptions théoriques
Keywords: Epistemologia; AD brasileira; Acontecimento; Prática científica; Epistemology; Brazilian DA; Event; Scientific practice; Épistémologie; AD brésilienne; Événement; Pratique scientifique; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA